Maternal Attitude and Knowledge towards Modes of Delivery - Joshi, Anshumala; Thapa, Meeta; Panta, Om Biju (Journal of Nepal Health Research Council, 2018)
Background: Whether a mother should be allowed to choose between the modes of delivery is a matter of concern among practicing obstetricians. This study aims to explore the knowledge of the Nepalese women attending a tertiary care center about the benefits and complications of vaginal and caesarean delivery and their attitude and preference for the method of delivery.Methods: The study was a hospital based cross sectional questionnaire survey conducted in Nepal Medical College teaching Hospital, Jorpati from 1stShrawan 2074 to 31st Ashoj 2074. All pregnant women who were 36 weeks or more in gestation attending the clinic during the study period were included in the study. A questionnaire was made of 10 questions for knowledge assessment regarding mode of delivery consisting of the indications, the possible complications and advantages of vaginal and caesarean delivery. Results: A total of 256 pregnant women participated in the study. The knowledge of the mode of delivery, their benefit and complications was medium to good in approximately 90% of the mothers attending the antenatal OPD. Overall attitude for vaginal delivery was positive in 93% of women and negative or neutral in 6.6%.Overall attitude for caesarean delivery was positive in 24% and negative or neutral in 75.8%.Conclusions: Women in our setup agree that vaginal delivery is a natural and acceptable method of delivery and would prefer to have a vaginal delivery. Keywords: Attitude; knowledge; modes of delivery; women.